Sensitivity to Activated Protein C; Influence of Oral Contraceptives and Sex - Henkens, C M A; Bom, V J J; Seinen, A J; van der Meer, J (Thrombosis and Haemostasis, 1995)
We investigated sensitivity to activated protein C (APC) in 43 men, 42 women not using oral contraceptives (OC) and 38 women using OC containing 30.0-37.5 μg ethinyl estradiol. A commercially available kit was used. Men were more sensitive to APC as compared with women not using OC (p <0.005), but this difference seems not to be of clinical importance. Women using OC showed to be significantly less sensitive to APC, reflected by a lower APC-ratio, as compared with men (p <0.005) and women not using OC (p <0.05).So, in normal individuals the APC-sensitivity differs according to sex and estrogen intake. This should be taken into account when interpreting APC-ratios.